posted by Anonymous .
*simplify by combining like terms, if possible. then, remove the GCF and factor fully.
...i'm not sure what to do after that, could you help and show the steps please
3x^2-21x+36 GCF: 3, so divide the whole thing by 3.
(What two #s add up to -7 and multiplied equal 12? 3 and 4)
[x^2-4x] - [3x+12]
x(x-4) - 3(x-4)
x-4= 4 x-3= 3 Answer X=3 and 4
I thought it said, factor fully.
3x^2 - 21x + 36 , which is correct
= 3(x^2 - 7x + 12)
nothing was said about "solving" the equation, since there was no equation.